PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI MASA PANDEMI PADA CV. MITRA MANDIRI MACHINERY PARTS AND SUPPLIER - Sugiharto, Fadira Az Zahra Putri; Waspodo Tjipto Subroto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of leadership and job satisfaction onemployee performance. The sample in this study were 27 people from CV. Mitra Mandiri Machinery Parts and Suppliers. The technical analysis used in this study is multiple linear regression using SPSS 25.The results of this study indicate that the independent variables simultaneously have an influence on employee performance. And partially, leadership has no significant effect on performance and job satisfaction has a significant effect on employee performance.